Occupational noise management: A preliminary study on compliance with hearing conservation programme in Malaysia’s manufacturing industry - Ismail, Noraidah; Newall, Philip; Zakaria, Mohd Normani (Nova Science Publishers, 2022)
Occupational noise hazards are one of the most common workplace safety concerns. Prolonged exposure to loud noise without adequate hearing protection can result in either temporary or permanent hearing loss. Using data collected from a sample of 27 safety officers from manufacturing companies in Malaysia, the present study aimed to examine the implementation of occupational noise management in Malaysia’s industry by evaluating their compliance with elements of hearing conservation programme (HCP). The results showed only 67% of the companies had a noise control policy despite the noise levels reported exceeding the permissible exposure level. Hearing protection device (HPD) usage was reported by most of the companies indicating their awareness towards danger posed by high noise levels. While international companies indicated greater compliance with appropriate occupational noise management practice, small and locally owned companies lagged behind and may require further guidance and assistance in implementing a better occupational noise management programme. Additionally, the present study found that the level of occupational noise awareness among the management of locally owned companies was low. This finding requires attention from policy makers with regard to the importance of regular checks and enforcement of noise regulations in the industry.